Phenoxybenzamine in Complex Regional Pain Syndrome: Potential Role and Novel Mechanisms - Mario A. Inchiosa (Anesthesiology Research and Practice)
There is a relatively long history of the use of the α-adrenergic antagonist, phenoxybenzamine, for the treatment of complex regional pain syndrome (CRPS). One form of this syndrome, CRPS I, was originally termed reflex sympathetic dystrophy (RSD) because of an apparent dysregulation of the sympathetic nervous system in the region of an extremity that had been subjected to an injury or surgical procedure. The syndrome develops in the absence of any apparent continuation of the inciting trauma. Hallmarks of the condition are allodynia (pain perceived from a nonpainful stimulus) and hyperalgesia (exaggerated pain response to a painful stimulus). In addition to severe, unremitting burning pain, the affected limb is typically warm and edematous in the early weeks after trauma but then progresses to a primarily cold, dry limb in later weeks and months. The later stages are frequently characterized by changes to skin texture and nail deformities, hypertrichosis, muscle atrophy, and bone demineralization. Earlier treatments of CRPS syndromes were primarily focused on blocking sympathetic outflow to an affected extremity. The use of an α-adrenergic antagonist such as phenoxybenzamine followed from this perspective. However, the current consensus on the etiology of CRPS favors an interpretation of the symptomatology as an evidence of decreased sympathetic activity to the injured limb and a resulting upregulation of adrenergic sensitivity. The clinical use of phenoxybenzamine for the treatment of CRPS is reviewed, and mechanisms of action that include potential immunomodulatory/anti-inflammatory effects are presented. Also, a recent study identified phenoxybenzamine as a potential intervention for pain mediation from its effects on gene expression in human cell lines; on this basis, it was tested and found to be capable of reducing pain behavior in a classical animal model of chronic pain.